Identifikasi Bahaya dan Pengendalian Risiko Keselamatan dan Kesehatan Kerja (K3) pada PT. PLN (Persero) - Akmal, Abdiel Khaleil; Ardika, Jumelia; Ananda, Zulia; Arfiya, Hilda (Universitas Teuku Umar, 2025)
The role of the workforce in supporting National Development is highly important, including the workers at PT. PLN (Persero) Transmission and Substation Meulaboh. It is necessary to provide occupational safety and health protection to workers in order to increase their productivity. This study aims to explain the importance of occupational safety and health protection in controlling hazard risks in the work environment of PT. PLN (Persero) Transmission and Substation Meulaboh. The research was conducted through direct observation and interviews, then analyzed using legal theory. The results show that there are still challenges in implementing occupational safety and health at PT. PLN (Persero) Transmission and Substation Meulaboh, such as the vast working area, employee relocation, and lack of awareness regarding the importance of using personal protective equipment (PPE). These challenges must be addressed through innovations in remote supervision and awareness campaigns to improve understanding of occupational safety and health, particularly the use of PPE.